Non-Invasive Ring Electrode With a Wireless Electrical Recording and Stimulating System for Monitoring Preterm Labor - Lee, Yijae; Lee, Changhyuk; Wang, Eun Jin; Kotov, Dmytro; Kim, Hee Youn; Hwang, Jeong Ho; Ahn, Ki Hoon; Lee, Soo Hyun (Institute of Electrical and Electronics Engineers, 2020)
Preterm labor and birth are the primary causes of neonatal morbidities and mortalities. The early detection and treatment of preterm uterine muscular contraction are crucial for the management of preterm labor. In this work, a ring electrode with a wireless electrical recording and stimulating (RE-WERS) system was designed, fabricated, and investigated for the non-invasive monitoring of uterine contraction/relaxation as a diagnostic and therapeutic tool for preterm labor. By using an organ bath system, we confirmed that the uterine contraction force in mice can be decreased by the application of electrical stimulation. Then, the RE-WERS system was inserted non-invasively through the vagina to the cervix of a pregnant minipig, and it successfully recorded the uterine contraction and reflect signals when various electrical stimulating conditions were applied. The difference in the uterine signals before and after the injection of a labor induction drug, such as oxytocin and prostaglandin F2 alpha, was recorded, and the difference was remarkable. In addition, the uterine signal that was recorded was well matched with the signal of the electromyography (EMG) kit during open abdominal surgery. It seemed that the continuous and various electrical stimulations affected the delay or inhibition of childbirth in the pregnant minipig.